Ethical perspective and values in hazardous waste management: Environmental racism - M. Gameil, Abeir Hussein; Kabbashi, Nassereldeen Ahmed (2013)
Allocation of land for the disposal and treatment of toxic waste is difficult in many developed nations; this more than often leads to dumping of the said waste into either the ocean or into developing nations. The latter option being the easier and more cost-effective of the two, due to the lack or lax of related regulations, the ethical aspect of this is often neglected. The questions to be asked then: Is it important to sustain life in the oceans at the cost of the survival of fellow human beings? Should there be such a term as legally-dumped hazardous waste? At what points can the engineer(s) intervene? This paper seeks to re-emphasize the ethical issues of hazardous waste management, specifically the dumping of toxic waste in developing nations, by offering practical answers to the above questions as well as many others. The paper aims to reach out to the individuals, i.e. the engineers, whom are capable of intervention, be it by prevention, and/or innovation of invention. Engineers have the obligation of finding more sustainable, practical solutions in terms of cost & environmental impact. Engineers also have the responsibility of exercising their right of whistle blowing, when necessary. The economic aspect, as well, cannot be neglected if a solution that satisfies all is sought; this means that developing nations should be provided with an alternative to the state of always being in debt and, consequently, dependent on Developed Nations; which is often the argument from their side on why they’d accept such an unethical proposal as to allow dumping of toxic waste in their lands, and as a result the emergence of many strange diseases, destruction of the environment, pollution of aquatic life, and climatic changes worldwide will be the payback.